Optimalisasi Produksi dan Pemasaran Sabun Organik Eco Enzyme di Kota Tomohon - Palandi, Reky Royke; Pareta, Douglas N; Kanter, Jabes; Korua, Sammy Rommy Novie (Universitas Klabat, 2024)
This community service aims to optimize the production and marketing of organic soap made from eco enzymes in Tumatangtang Satu Village, Tomohon City. This organic soap is produced through the use of eco enzymes from abundant fruit and vegetable waste in the area. Although the business has been running, production is still limited to a home scale, and marketing is not optimal. The program includes the procurement of new equipment, production skills training, and the utilization of digital platforms for marketing. The results of this activity are expected to increase production up to 150 soaps per day and increase market reach through digital marketing.